Teaching psycholinguistics as a method of professional competence development of medical psychologists - Elena A. Sloeva; Natalia V. Pryadilnikova; Alexey A. Boklin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the aspects of teaching of psycholinguistics as a discipline that promotes the development of professional competences of the students of medical university. The structure of the course, its content and thematic content is described. The samples of different-level tasks for students are suggested. The tasks are based on the study conducted at the Department of Psychiatry, Addiction, Psychotherapy and Clinical Psychology in cooperation with the Department of Pedagogy, Psychology and Psycholinguistics of SSMU and the Department of Publishing of SSAU.